Epidermal galactose spurs chytrid virulence and predicts amphibian colonization - Yu Wang (Nature Portfolio, 2021)
The skin disease chytridiomycosis is linked to global amphibian declines but effective mitigation measures require improved understanding of the mechanisms underpinning the disease ecology. This study identifies key mediators of interactions between the fungal pathogen and amphibian skin, providing a marker of host colonization that can predict susceptibility between amphibian species.